Absattar Derbisali and kazakh oriental studies. - Salkynbayev., M. B. (Journal of Oriental Studies, 2016)
This article submit an analysis of scientific works of the famous scientist and one of the founders of Kazakh Oriental Studies Absattar kazhy Derbіsalі . And also investigated scientific values such as his monograph “Arab adebietі “, “Arabic-language literature of Morocco” and fundamental work such works as “ Shynyrau bulaktar “, “Kazak dalasynyn zhuldyzdary” and etc.